Early Onset Scoliosis: Is there an Improvement in Quality of Life With Conversion From Traditional Growing Rods to Magnetically Controlled Growing Rods?. Issue 4 (April 2019) - Bauer, Jennifer M.; Yorgova, Petya; Neiss, Geraldine; Rogers, Kenneth; Sturm, Peter F.; Sponseller, Paul D.; Luhmann, Scott; Pawelek, Jeff B.; Shah, Suken A.
Abstract : Background: Modern treatment of early onset scoliosis (EOS) includes implantation of traditional growing rods (TGR) or magnetically controlled growing rods (MCGR) for posterior-based distraction if nonoperative treatment plans failed. The recent MCGR innovation has largely been expected to improve patient and family burden by avoiding frequent return to the operating room. At least one study has shown no HRQoL difference between TGR and MCGR, but none have specifically investigated a cohort of conversion patients whose families have experienced both. Methods: An EOS database was queried for all patients treated with TGR, MCGR, and those converted from TGR to MCGR who had at least 1 pretreatment and 1 posttreatment HRQoL assessment (EOSQ-24). Data on demographics, diagnoses, and major curve size, as well as EOSQ-24 domain scores were studied. Results: There were 156 TGR, 114 MCGR, and 32 conversion patients, with an average of 2.0 years between first and final EOSQ-24 surveys. There was no significant difference in outcome in any EOSQ-24 domain between the converts and the other 2 treatment groups. There was a significant post-op improvement in MCGR versus TGR in transfers and energy level ( P =0.01; P =0.01). Conclusions: Although patient families and their surgeons may subjectively report improved HRQoL after conversion from TGR lengthenings to in-office MCGR lengthenings, these improvements were seen in transfer and fatigue domains, not burden or satisfaction. Although the EOSQ-24 is a well-validated EOS metric, it may not be sensitive enough to overcome the QoL floor-effect associated with the diagnosis itself, or perhaps the improvement in QoL must be assessed over a longer interval to assess meaningful change. Level of Evidence: Level III—retrospective comparative study.